Focal-plane multibeam dual-band dielectric lens for ka-band - Cruz, C. C.; Costa, J. R.; Fernandes, C. A.; Matos, S. (IEEE Antennas and Wireless Propagation Letters, 2017)
A shaped double-shell dielectric lens is evaluated as a primary feed for a multibeam single-reflector system operating in the satellite uplink and downlink Ka-bands, complying with gain and edge-of-coverage (EoC) directivity requirements. An assembly of dual-band printed feeds is integrated at the base of a single lens, each feed producing a virtual focus far behind the lens base and coincident with the reflector focal arch. The used double-shell lens approach, instead of a single-material lens, allows an extra degree of freedom to accommodate an aberration mitigation condition. This primary feed system is proposed as a low-complexity solution to enable fitting more beams per solid angle than conventional single-feed-per-beam systems based on a cluster of focal-plane horns. A proof-of-concept lens prototype with 87mm diameter and 62 mm height, fed by a linear arrangement of five dual-band printed feeds, was fabricated and tested at the Ka-band. The lens measured radiation patterns were post-processed to evaluate the combined performance of the lens with an offset F/D = 1 reflector system designed for 45 dBi EoC directivity. It is shown that it duplicates the reflector aperture efficiency compared to horn-fed systems with same feed separation.